Molecular characterization of DDX26, a human DEAD-box RNA helicase, located on chromosome 7p12 - Camargo,A.A. (2001)
DEAD-box proteins comprise a family of ATP-dependent RNA helicases involved in several aspects of RNA metabolism. Here we report the characterization of the human DEAD-box RNA helicase DDX26. The gene is composed of 14 exons distributed over an extension of 8,123 bp of genomic sequence and encodes a transcript of 1.8 kb that is expressed in all tissues evaluated. The predicted amino acid sequence shows a high similarity to a yeast DEAD-box RNA helicase (Dbp9b) involved in ribosome biogenesis. The new helicase maps to 7p12, a region of frequent chromosome amplifications in glioblastomas involving the epidermal growth factor receptor (EGFR) gene. Nevertheless, co-amplification of DDX26 with EGFR was not detected in nine tumors analyzed.